Passive borate-based salt as electrolyte alternative for zero-excess lithium metal battery - Natarajan, Karthic; Wu, She–Huang; Wu, Yi–Shiuan; Chang, Jeng-Kuei; Jose, Rajan; Yang, Chun-Chen (Elsevier Ltd, 2025)
Anode-free lithium–metal batteries (AFLMBs) are ideal candidates for achieving high-energy density electrochemical energy storage (EES) devices by eliminating the need for a conventional graphite electrode or excess lithium–metal anode. Those AFLMBs severely suffer from low Coulombic efficiency (CE), and long cyclability due to the loss of Li inventory in the cathode to uncontrollable side reactions. Advanced electrolyte development is a promising route to maximize lithium-inventory retention rate (LIRR) and minimize capacity fade. However, a poor understanding of the mechanisms by which advanced electrolytes improve performance hampers progress in the practical development of AFLMBs. In this study, the 1 M LiDFOB in EC/DMC (1:1, v/v %) + 1 wt% LiDFP +1 wt% FEC (denoted as DDEDF) has been chosen as an alternative liquid electrolyte for AFLMBs. The electrolyte properties of the DDEDF electrolyte in asymmetric and symmetric configurations were systematically studied and compared with the electrochemical performances of conventional LP30 electrolyte (1 M LiPF6 in EC/DMC (1:1, v/v %)) used for LMBs. The AFLMB based on DDEDF electrolyte delivered an enhanced cyclability (100 cycles) and superior LIRR retention (99.10 %) than the LP30 electrolyte. Based on those results, we found that our DDEDF shows highly promising as an alternative liquid electrolyte for the AFLMB practical application.